Backstepping control for a 3DOF model helicopter with input and output constraints. (1st February 2016) - Mei, Rong; Cui, Qingliang
In this article, a backstepping control scheme is developed for the motion control of a Three degrees of freedom (3DOF) model helicopter with unknown external disturbance, modelling uncertainties and input and output constraints. In the developed robust control scheme, augmented state observers are applied to estimate the unknown states, unknown external disturbance and modelling uncertainties. Auxiliary systems are designed to deal with input saturation. A barrier Lyapunov function is employed to handle the output saturation. The stability of closed-loop system is proved by the Lyapunov method. Simulation results show that the designed control scheme is effective at dealing with the motion control of a 3DOF model helicopter in the presence of unknown external disturbance and modelling uncertainties, and input and output saturation.